2014
DOI: 10.5489/cuaj.1679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of robotic and open partial nephrectomy: Single-surgeon matched cohort study

Abstract: Results: There was no significant difference between the 2 cohorts with respect to patient age, BMI, ASA score, preoperative glomerular filtration rate, tumour size and the R.E.N.A.L. nephrometry score. The mean operative time was longer in the RPN group, but there were no significant differences with respect to warm ischemic time and postoperative renal function. The length of hospitalization and use of postoperative analgesics (ketoprofen) were more favourable in the RPN cohort. There was no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
(34 reference statements)
5
7
1
Order By: Relevance
“…Only blood loss was no longer statistically significant between OPN and RAPN after propensity score matching, and it remained slightly lower for RAPN (250 vs. 300 ml, see Table ) 27 . Operating time and WIT were longer for RAPN, which is in line with other studies 23,28 . RAPN still had fewer postoperative complications than OPN ( p < 0.001), which has been published for (highly) complex lesions 29,30 .…”
Section: Discussionsupporting
confidence: 82%
“…Only blood loss was no longer statistically significant between OPN and RAPN after propensity score matching, and it remained slightly lower for RAPN (250 vs. 300 ml, see Table ) 27 . Operating time and WIT were longer for RAPN, which is in line with other studies 23,28 . RAPN still had fewer postoperative complications than OPN ( p < 0.001), which has been published for (highly) complex lesions 29,30 .…”
Section: Discussionsupporting
confidence: 82%
“…2f ). The overall warm ischemia time of RAPN was significantly longer than that of OPN (WMD, 2.18 min; 95 % CI, 0.49 to 3.87; p = 0.01) as supported by the pooled data from 10 studies [ 6 , 8 , 9 , 11 , 12 , 19 , 20 , 23 , 24 ] (Fig. 2g ).…”
Section: Resultssupporting
confidence: 55%
“…2c ) was found in the RAPN group. Eight studies [ 8 , 10 , 17 , 19 21 , 23 , 24 ] examined the perioperative transfusion, and we found that there was no significant difference in transfusion rate between RAPN and OPN (OR, 0.86; 95 % CI, 0.56 to 1.32; p = 0.50) (Fig. 2d ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…RAPN has now begun to be an alternative option to OPN because robot can offer a three-dimensional view of the operating field and fully flexible wristed-instrument motion, and overcome the learning curve for LPN ( 14 ). Several previous studies have compared RAPN with OPN and support the trend of increased use of RAPN ( 15 16 17 18 ).…”
Section: Discussionmentioning
confidence: 75%